1996
DOI: 10.1037/0735-7044.110.6.1349
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ventral tegmental area dopamine neurons to expression of conditional fear: Effects of electrical stimulation, excitotoxin lesions, and quinpirole infusion on potentiated startle in rats.

Abstract: Potentiated startle was used in this study to determine the fear-motivational functions of the ventral tegmental area (VTA). In Experiment 1, electrical stimulation of the VTA increased acoustic startle amplitudes. In subsequent experiments fear-potentiated startle was assessed following axon-sparing N-methyl-D-aspartic acid (NMDA) lesions of the VTA and after bilateral intra-VTA infusion of the dopamine (DA) D2/3 receptor agonist quinpirole. The NMDA lesions produced substantial cell loss in the medial ventra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 63 publications
3
53
0
3
Order By: Relevance
“…Furthermore, reduced dopaminergic signaling in the NAc is associated with emotional signs of nicotine withdrawal (Cryan et al, 2003;Paterson et al, 2007). Further confirmation that the mesolimbic dopaminergic system contributes to withdrawal from other addictive drugs would cohere with a growing body of literature demonstrating that it is also involved in a wide variety of aversive behaviors, including conditioned place aversion (Acquas et al, 1989;Calcagnetti and Schechter, 1991;Schechter and Meechan, 1994;Liu et al, 2008), fear conditioning (Borowski and Kokkinidis, 1996;Nader and LeDoux, 1999;Pezze and Feldon, 2004;Fadok et al, 2009;Muschamp et al, 2011), anxiety (Fride and Weinstock, 1988;Barrot et al, 2002;Barrot et al, 2005;Meloni et al, 2006;Rezayof et al, 2009;Richard and Berridge, 2011;Zweifel et al, 2011), intrinsic aversion to gustatory cues (Roitman et al, 2008), conditioned taste aversion Fenu et al, 2001), responses to stress (Geyer and Segal, 1974;Herman et al, 1982;Inglis and Moghaddam, 1999;Belda and Armario, 2009), and responses to nociceptive stimulation (Gear et al, 1999;Becerra et al, 2001;Barrot et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, reduced dopaminergic signaling in the NAc is associated with emotional signs of nicotine withdrawal (Cryan et al, 2003;Paterson et al, 2007). Further confirmation that the mesolimbic dopaminergic system contributes to withdrawal from other addictive drugs would cohere with a growing body of literature demonstrating that it is also involved in a wide variety of aversive behaviors, including conditioned place aversion (Acquas et al, 1989;Calcagnetti and Schechter, 1991;Schechter and Meechan, 1994;Liu et al, 2008), fear conditioning (Borowski and Kokkinidis, 1996;Nader and LeDoux, 1999;Pezze and Feldon, 2004;Fadok et al, 2009;Muschamp et al, 2011), anxiety (Fride and Weinstock, 1988;Barrot et al, 2002;Barrot et al, 2005;Meloni et al, 2006;Rezayof et al, 2009;Richard and Berridge, 2011;Zweifel et al, 2011), intrinsic aversion to gustatory cues (Roitman et al, 2008), conditioned taste aversion Fenu et al, 2001), responses to stress (Geyer and Segal, 1974;Herman et al, 1982;Inglis and Moghaddam, 1999;Belda and Armario, 2009), and responses to nociceptive stimulation (Gear et al, 1999;Becerra et al, 2001;Barrot et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…For example, lesions to the VTA were shown to inhibit fear-potentiated startle in rats [11]. Also, cocaine administered repeatedly over 5-7 days, but not acutely on a single day, facilitated LTP induction in VTA dopamine neurons [33].…”
Section: Discussionmentioning
confidence: 99%
“…While the impact of monoamine alterations on conditioned fear is far from clear, past studies investigating the influence of DA on cued conditioning suggest that decreases (Davis et al, 1993;Borowski and Kokkinidis, 1996;Munro and Kokkinidis, 1997), but not increases in DA mesolimbic activity may produce impairments. Concerning alterations in serotonergic activity, results obtained using the fear-potentiated startle paradigm have shown that systemic injections of buspirone, a partial 5-HT1A receptor agonist, block fear-potentiated startle Mansbach and Geyer, 1988;Risbrough et al, 2003).…”
Section: Discussionmentioning
confidence: 99%